Deciphering the heterogeneity of myeloid cells during neuroinflammation in the single‐cell era - Borst, Katharina; Prinz, Marco (Brain pathology (Zurich, Switzerland), 2020)
Multiple sclerosis (MS) is a disabling neuroinflammatory disease, which is little understood and lacks a sufficient therapeutic regimen. Myeloid cells have repeatedly shown to play a pivotal role in the disease progression. During homeostasis, only the CNS‐resident microglia and CNS‐associated macrophages are present in the CNS. Neuroinflammation causes peripheral immune cells to infiltrate the CNS contributing to disease progression and neurological sequelae. The differential involvement of the diverse peripheral and resident myeloid cell subsets to the disease pathogenesis and outcome are highly debated and difficult to assess. However, novel technological advances (new mouse models, single‐cell RNA‐Sequencing, and CYTOF) have improved the depth of immune profiling, which allows the characterization of distinct myeloid subsets. This review provides an overview of current knowledge on the phenotypes and roles of these different myeloid subsets in neuroinflammatory disease and their therapeutic relevance. This review provides an overview of current knowledge on the phenotypes and roles of different myeloid subsets in neuroinflammatory disease and their therapeutic relevance.